0083 Acoustically Induced Changes In Sleep Spindle And Autonomic Activity Predict Memory Consolidation. (27th April 2018) - Papalambros, N A; Grimaldi, D; Reid, K J; Abbott, S M; Malkani, R G; Santostasi, G; Gendy, M; Ritger, A; Braun, R; Sanchez, D; Paller, K A; Zee, P C
Abstract: Introduction: Acoustic stimulation during sleep has been shown to enhance memory consolidation. Autonomic function has been shown to play a role in sleep dependent memory. We postulate that acoustically induced changes in sleep interact with autonomic function to enhance memory. We examined the contribution of slow-wave, spindle activity, and a vagally mediated index of heart rate variability (HRV) on memory consolidation following acoustic stimulation. Methods: Twenty subjects (25 ± 4 years, 75% female) participated in a cross-over study with two 2-night visits. After one night of adaptation, participants were randomized to receive either stimulation (stim) or sham on the following night. Stim occurred in blocks of 5 pulses ("ON interval") followed by a refractory period of equal length ("OFF interval") during NREM sleep. Participants learned 40 Arabic-English word pairs and were tested before and after sleep. Spectral analysis and spindle (11-15Hz) detection were performed during ON intervals for both conditions. Polysomnography was used to calculate sleep stages and arousal index (number/hour). A HRV-derived index (high frequency power (HF)), was quantified during stable slow-wave sleep (SWS). Regression analyses were used to develop models that could predict overnight memory improvement. Results: Stim increased slower frequency (0.5-7Hz) and spindle power in ON intervals compared to sham (p<0.001). Stim increased spindle density during ON intervals (5.8 v. 4.9 number/min) and HF power (71.3% v. 61.7%), along with the arousal index (12.6 v. 10.4) compared to sham (p<0.01). Overnight mean (SD) percent improvement in word recall was similar between conditions (Stim: 5 (11.4)% v. Sham: 5.6 (4.6)%, p=0.5). However, in the stim condition, a model that included sleep spindle density during ON intervals (β=5.88, p=0.002) and HF power during SWS (β=5.0, p=0.04), after adjusting for the total arousal index (β=1.47, p=0.002) accounted for 60% of the variance in overnight memory improvement [adjusted R 2 =0.60, p=0.0002]. Conclusion: Acoustic stimulation during sleep alters both sleep and autonomic features that contribute to sleep dependent improvement in memory. A better characterization of the sleep-autonomic interaction is important for understanding the mechanisms involved in memory consolidation. Support (If Any): W911NF-16-2-0021, NIH T32 NS047987, NSF GRFP DGE-1324585.